2016
DOI: 10.4306/pi.2016.13.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Increased Neutrophil/Lymphocyte Ratio in Patients with Depression is Correlated with the Severity of Depression and Cardiovascular Risk Factors

Abstract: ObjectiveChronic inflammation is associated with cardiovascular (CV) risk factors and psychiatric disorders. The neutrophil to lymphocyte ratio (NLR) has been investigated as a new biomarker for systemic inflammatory response. The aim of the study is to investigate the relation of NLR with severity of depression and CV risk factors.MethodsThe study population consisted of 256 patients with depressive disorder. Patients were evaluated with the Hamilton Rating Scale for Depression (HAM-D). Patients were classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 28 publications
(32 reference statements)
2
50
1
2
Order By: Relevance
“…Compared with normal controls, NLR was significantly higher in patients with MDD, and then reduced to the control group's level after treatment with selective serotonin inhibitors (SSRIs), accompanied by remission of depressive symptoms (Demircan et al, 2016). In addition, multiple studies have shown the same association between increased NLR and depression (Demir et al, 2015;Aydin et al, 2016;Ekinci and Ekinci, 2017). A recently published study showed that NLR was associated with depression in female Chinese adults (aged 40.5 ± 11.6 years) (Meng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with normal controls, NLR was significantly higher in patients with MDD, and then reduced to the control group's level after treatment with selective serotonin inhibitors (SSRIs), accompanied by remission of depressive symptoms (Demircan et al, 2016). In addition, multiple studies have shown the same association between increased NLR and depression (Demir et al, 2015;Aydin et al, 2016;Ekinci and Ekinci, 2017). A recently published study showed that NLR was associated with depression in female Chinese adults (aged 40.5 ± 11.6 years) (Meng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with MDD had higher NLR as compared with healthy controls (17). Another study compared the severity of depression and cardiovascular risk factors with NLR value and found a positive correlation (18). As far as we know there has not been published any article about monocyte/lymphocyte ratio (MLR) in MDD yet.…”
Section: Introductionmentioning
confidence: 99%
“…One study reports that the increased neutrophil/lymphocyte ratio is correlated with the severity of depression in patients with depression [18]. As one of the important indicator of inflammation, neutrophilic granulocyte percentage is cheap and simple test contained in blood routine test.…”
Section: Introductionmentioning
confidence: 99%